2022
DOI: 10.29240/ef.v6i2.5452
|View full text |Cite
|
Sign up to set email alerts
|

English Teachers' Perception of Implementing Project-Based Learning in Secondary Schools

Abstract: The aims of this study were to investigate English teachers’ perceptions in implementing Project-Based Learning and to analyze the English teachers’ challenges of implementing Project-Based Learning in Secondary Schools in Bengkulu City. 16 English teachers in Senior High Schools and 14 English teachers in Junior High Schools who have implemented Project-Based Learning in their class served as participants in this study. An explanatory sequential mixed method research applied to investigate the teachers’ perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…This condition aligned with what PjBL promoted, that is, the use of student-centered learning in the class as student is able to construct investigation, to set a goal and acts as an autonomous learner within real-world practices (Kokotsaki et al, 2016). Similar studies confirmed that students believed teachers gave them freedom to choose and develop content inside their project in PjBL learning process (Sartika et al, 2022;Hidayati et al, 2023). Moreover, when student are given freedom to choose, students most likely shared that they appreciated the opportunity to research what they wanted (DeMink & Olofson, 2020).…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…This condition aligned with what PjBL promoted, that is, the use of student-centered learning in the class as student is able to construct investigation, to set a goal and acts as an autonomous learner within real-world practices (Kokotsaki et al, 2016). Similar studies confirmed that students believed teachers gave them freedom to choose and develop content inside their project in PjBL learning process (Sartika et al, 2022;Hidayati et al, 2023). Moreover, when student are given freedom to choose, students most likely shared that they appreciated the opportunity to research what they wanted (DeMink & Olofson, 2020).…”
Section: Discussionsupporting
confidence: 69%
“…Students also responded positively towards their teachers implementing PjBL. Students believed teachers gave them freedom to choose and develop content inside their project (Sartika et al, 2022;Hidayati et al, 2023). Students also show tendency to agree on how teacher used varied material resources and internet in researching and finishing projects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various implementations of PjBL in junior high school learning have been carried out, both in the Indonesian and global contexts. There is research focused on how teachers implement projects (Markula & Aksela, 2022), teach speaking a spoken advertisement (Humairoh & Purwati, 2014), teachers' perception (Sartika et al, 2022), gadget play duration survey (Sitio et al, 2023), EFL classroom (Wijayanti & Budi, 2023), language learning (Ukah et al, 2023), teaching speaking to young learners (Widiyati & Pangesti, 2022), PjBL in in robotics meets (Zadok, 2020), music learning (Banua et al, 2023;Nugroho & Dewi, 2022), and management of project-based learning model at Sekolah Alam (Ahmad, 2021). In terms of abilities or competencies of junior high school students, PjBL research is focused on creative thinking skills (Biazus & Mahtari, 2022), critical thinking skills (Wibowo et al, 2018) and cooperative skills (Indriyana & Susilowati, 2020), students' engagement and speaking competence (Bunyamin, 2022), communication skills (Pratiwi et al, 2020), and collaboration, creativity, and computational thinking (Alkautsar et al, 2023).…”
Section: Introductionmentioning
confidence: 99%